Traceability simulation of drainage in irrigation areas along the south bank of the Yellow River based on the SWAT model - Hexiang, Zheng; Yujing, Han; Rongxuan, Bao; Biyu, Wang; Jiabin, Wu; Delong, Tian; Haofang, Yan; Beibei, Hao (Frontiers in Environmental Science, 2025)
The simulation of drainage sources in irrigation areas at the watershed scale is of great significance for understanding the characteristics and drainage status of irrigation districts under various water-saving irrigation and climatic conditions. In this study, our focus was on the irrigation areas located on the south bank of the Yellow River in Hangjin Banner. We aimed to analyze and simulate the flow rate and overall drainage volume in the drainage ditch by developing a soil and water assessment tool (SWAT) model. The measured drainage data were utilized to calibrate and validate the model to explore the structure and sources of drainage in the selected study area. The results indicated that the average annual drainage volume of the study area was 4355.65 × 104 m³, and the primary source of drainage was subsurface drainage, which accounted for approximately 68% of the total drainage. Subsurface flow was the second-largest source, contributing approximately 31%, while surface drainage accounted for a negligible proportion, contributing merely 1% to the drainage. Concerning the proportion of drainage relative to the total drainage in each irrigation area, the Balahey irrigation area accounted for approximately 20%, the Jianshe irrigation area for approximately 45%, and the Dugui irrigation area for approximately 35%. Moreover, the model parameters were optimized using SWAT-CUP software to obtain the R2, NSE, Re, and RMSE values of 0.65, 0.60, −8.54%, and 384.65 × 104 m3, respectively, for the model calibration period, and the corresponding values were 0.63, 0.56, −7.82%, and 389.65 × 104 m3, respectively, for the validation period. The traceability simulation results for irrigation drainage are of crucial importance for the efficient utilization of water resources in this study area.